Navigating digital stress and the flexible work environment: increasing generation z and alpha productivity through adaptive communication - Gunawan, Kiki Gunawan; Martono, Besar Agung Martono (Enrichment : Journal of Management, 2025)
This study investigates the role of communication as a moderating variable in the influence of work stress and work environment on the productivity of Generation Z and Alpha. Using a quantitative approach with data from 41 assessors at the Cibubur Geospatial Professional Certification Institute (LSP), analyzed through SmartPLS 4.1.1.4, the findings reveal a moderating role at various levels of communication that is crucial for management in managing work stress and work environment in an effort to increase employee productivity. Stakeholders should pay attention on the effectiveness of communication to ensure stress management and work environment for ensuring high level of assessor productivity. The study limitated on the sample size and in one professional institution only. Hopefully, the future research can be continued in other types of businesses, with more globally respondents to refine the generalizations.